2005
DOI: 10.1152/ajpheart.00194.2005
|View full text |Cite
|
Sign up to set email alerts
|

Splanchnic hyperemia and hypervolemia during Valsalva maneuver in postural tachycardia syndrome

Abstract: Prior work demonstrated dependence of the change in blood pressure during the Valsalva maneuver (VM) on the extent of thoracic hypovolemia and splanchnic hypervolemia. Thoracic hypovolemia and splanchnic hypervolemia characterize certain patients with postural tachycardia syndrome (POTS) during orthostatic stress. These patients also experience abnormal phase II hypotension and phase IV hypertension during VM. We hypothesize that reduced splanchnic arterial resistance explains aberrant VM results in these pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…However, indirect measures of arm and leg peripheral vasoconstriction are at least consistent with the claim of sympathoexcitation, as are observed heart rate and BP variability data. Prior published work indicates exaggerated vasoconstriction in comparable normal-flow POTS patients during phase II of the Valsalva maneuver (34).…”
Section: Limitationsmentioning
confidence: 90%
See 2 more Smart Citations
“…However, indirect measures of arm and leg peripheral vasoconstriction are at least consistent with the claim of sympathoexcitation, as are observed heart rate and BP variability data. Prior published work indicates exaggerated vasoconstriction in comparable normal-flow POTS patients during phase II of the Valsalva maneuver (34).…”
Section: Limitationsmentioning
confidence: 90%
“…Methods have recently been validated in our laboratory for the detection of leg, thoracic, and splanchnic blood flow (33,34). Pulsatile changes in electrical resistance for each segment were employed to compute the time derivative ‫ץ‬R/‫ץ‬t, which we used to obtain the blood flow responses of each body segment during tilt.…”
Section: Details Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent clinical trial by Stewart et al suggested that splanchnic hyperemia during tilt table testing might correlate with the rapid decrease in BP after a Valsalva maneuver in a subset of patients with POTS. 58 A second type of POTS referred to as the "␤-hypersensitivity" form is believed to be due to an inadequate feedback process that arises from above the level of the baroreflex. 59 Thus far, treatment of POTS remains largely supportive and palliative, although recent studies have shown some success with acetylcholinesterase inhibition 60 and selective serotonin reuptake inhibitors.…”
Section: Postural Tachycardia Syndrome (Pots)mentioning
confidence: 99%
“…They may develop significant hypotension in phase II of the manoeuvre and the overshoot in phase IV is also exaggerated. 18 A recent case report of a successful vaginal delivery used continuous low-dose epidural infusion and invasive blood pressure monitoring along with a forceps-assisted delivery to diminish the Valsalva manoeuvres made by the mother. 6 This mother had previously had a near cardiac arrest during normal vaginal delivery of her first baby before her condition was recognised.…”
Section: Discussionmentioning
confidence: 99%